Cotton growth and boron distribution in the plant as affected by a temporary deficiency of boron - Rosolem, Ciro Antonio [UNESP]; Costa, Antonio (Taylor & Francis, 2000)
The knowledge of nutrient mobility is an important tool to define the best fertilizer management and diagnosis techniques. Patterns of boron (B) mobility in plants have been reviewed, but there is very little information on B distribution and mobility in cotton. An experiment was conducted to study plant growth and B distribution in cotton when the nutrient was applied in the nutrient solution or to the leaves, and when a temporary deficiency was imposed. Cotton (Gossypium hirsutum, Latifolia, cv. IAC 22) was grown in nutrient solutions where B was omitted or not for 15 days. Boron was applied to young or mature cotton leaves in some of the minus B treatments. Root growth decreased when the plants were transferred to B solutions, but there was a full recovery when B was replaced in the nutrient medium. Boron deficiency, even when temporary, reduced cotton shoot dry matter yields, plant height and flower and fruit set, and these could not be prevented by foliar application of B. Because of decreased dry matter production, leaves of deficient cotton plants actually showed higher B concentrations than non deficient leaves. This would be misleading when a mature leaf is sampled for diagnosis. If there is any B mobility in cotton phloem, it is very low.
Keywords: Gossypium hirsutum